Language teachers’ surfing skills: teachers’ knowledge of metasearch engines and advanced search facilities - Wan Yusof, Wan Putri Zahra; Mat Daud, Nuraihan (2010)
The National Council for the Accreditation of Teachers (NCATE) (2008) recognises the relevance of incorporating the use of internet and world wide web in teacher training (ISTE, 2008). Brooks and Byles (2000) stress on productive strategies in Internet search. However, these are often overlooked although finding information on the Internet and how they work requires the right surfing skills. Added to that each search engine differs in its way of displaying information. A survey was conducted on all language teachers teaching at the Centre for Languages, IIUM to analyse teachers’ knowledge of available search engines and their surfing skills. Questionnaire survey and interview methods were adopted in this study. The study found that the majority of the teachers were not aware of the presence of search engines other than Yahoo, Google and MSN. Metasearch engines were rarely used. Many were also not aware of the advanced search facilities. They went for any domain and all formats when surfing without knowing that they could select for specific files and specific language when looking for materials. The research points to the need for teaching effective surfing skills in pre-service and in-service teacher training programmes.